PERAN TOKOH MASYARAKAT DALAM MELESTARIKAN TRADISI SAPRAHAN DI DESA PUSAKA KECAMATAN TEBAS - Legi Saputra; Gusti Budjang; Maria Ulfa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThe purpose of this study is to describe the role of community leaders in preserving the Saprahan tradition in Pusaka Village, Tebas District. The approach used in this research is qualitative with descriptive methods. The implementation process is carried out by observation, interview and documentation study. The results showed that the role of community leaders in maintaining and preserving the Saprahan tradition in the Pusaka Village of Tebas Subdistrict is to guide the community by providing guidance and teaching to the citizens of Pusaka Village about what and how the saprahan tradition is carried out, as a motivator for the community by intimate approaching with residents, exchanging ideas with residents at leisure, providing encouragement and input to citizens in carrying out events and as an umbrella in the tradition of saprahan, namely providing security to the community by protecting and taking full responsibility for the event held so that the event runs orderly and smoothly. Keywords : The Role of Public Figures, Saprahan Tradition